Small and Medium Sized European Firms and Energy Efficiency Measures: A Probit Analysis - Guglielmo Maria Caporale; Cristiana Donati; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the factors (such as different sources of financing, energy audits and internal monitoring activities) affecting the propensity of European small and medium sized enterprises (SMEs) to adopt energy efficiency measures (EEMs). For this purpose, a Probit model is estimated using data from the 2017 Flash Eurobarometer survey covering a large sample of European firms. The analysis is carried out for the full sample as well as for clusters based on an environmental performance index (EPI) and on the level of economic development in turn. The results indicate that internal financing always has a positive effect on a firm's propensity to adopt EEMs. Private external sources of financing appear to be more important for Western European firms as well as for those located in countries with a greater level of environmental awareness; in the latter, when firms combine private financing with energy audits or internal monitoring activities the propensity to adopt EEMs increases further. By contrast, in the Eastern Countries this occurs when firms simultaneously rely on public funds and monitoring activities.
Keywords: G32; O16; Q40; 330; energy efficiency measures; EPI; financing; SMEs